1991
DOI: 10.1002/pssa.2211250222
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Magnetic Properties of Submicron Grained Cobalt after Large Plastic Deformation and Their Variation during Annealing

Abstract: The microstructure and magnetic properties of cobalt deformed by torsion at high quasihydrostatic pressure and their variations during annealing are studied. A correlation between the hysteretic properties and microstructure after annealing at different temperatures is established. A delay of the γ‐ϵ polymorphous transformation is derived from the temperature dependence of magnetization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Vickers hardness at the saturated level (HV) of a wide range of pure metals and semi-metals with various crystal structures processed through severe plastic deformation (SPD) have been reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,66]. In this work, we study the increment of hardness (∆HV) of 17 high purity (better than 99.9%) elements due to HPT reported in [4,5,9,10,23,28,66] (see Table 1).…”
Section: Hardness Data Of Hpt Processed Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Vickers hardness at the saturated level (HV) of a wide range of pure metals and semi-metals with various crystal structures processed through severe plastic deformation (SPD) have been reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,66]. In this work, we study the increment of hardness (∆HV) of 17 high purity (better than 99.9%) elements due to HPT reported in [4,5,9,10,23,28,66] (see Table 1).…”
Section: Hardness Data Of Hpt Processed Metalsmentioning
confidence: 98%
“…Following extensive work in the field by a range of researchers, extensive data on the hardness and microstructure of HPT processed metals and alloys is now available (e.g. [4,5,6,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]). Data on hardness increase due to HPT have been published for over 20 pure metals, and several of the factors influencing the hardness of HPT processed pure metals have been investigated in some detail by Edelati and Horita [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…HPT processing significantly increases yield strength and hardness of nearly all metals and alloys. Microhardness of HPT processed metals are improved up to 100 % for pure Al [3,4], 130 % for pure Ti [5,6], 400 % for pure Fe [7] , 60 % for pure Cu [8], and also for a range of other metals strong hardening has been evidenced [9,10,11,12,13,14,15,16,17,18]. This is because the HPT process imposes a very large shear strain on the metal and a very large amount of dislocations and/or twins are generated in the metals, which further cause significant microstructure refinement.…”
mentioning
confidence: 99%
“…Ultrafine-grained microstructures, high strength and reasonable ductility are successfully attained in bulk pure metals through the application of high-pressure torsion (HPT). The HPT method, which was first introduced by Bridgman in 1935 [1], has been applied to a wide range of body-centered cubic (bcc) metals such as Fe [2], V [3], Nb [4], Cr [5], Mo [6] and W [7], face centered cubic (fcc) metals such as Al [8], Cu [9], Ag [10], Au [10], Ni [11], Pt [12] and Pd [13], hexagonal close-packed (hcp) metals such as Mg [14], Ti [15], Zr [16], Hf [17] and Co [18], and semi-metals with a diamond cubic structure such as Si [19] and Ge [20]. Earlier reports showed that the hardness variation is represented by a unique function of the equivalent strain in Fe [21], V [3], Mo [3], Al [22][23][24], Cu [25], Ag [12], Au [12], Ni [12], Pt [12], Ti [26], Zr [27] and Hf [17].…”
mentioning
confidence: 99%